Bridge maintenance, safety, management, health monitoring and informatics : proceedings of the Fourth International Conference on Bridge Maintenance, Safety and Management, Seoul, Korea, 13-17 July 2008 /: proceedings of the Fourth International Conference on Bridge Maintenance, Safety and Management, Seoul, Korea, 13-17 July 2008. (2008) - Unknown
No abstract available